God, Man, and Satan - Frye, Roland Mushat (Book collections on Project MUSE., 2016)
Treating John Milton's Paradise Lost as a Christian vision of reality and Bunyan's Pilgrim's Progress as an allegory of the Christian life, Roland Mushat Frye brings together two seventeenth-century works in this highly original literary study. He sees the writings both as art and as theological expression, and his analysis penetrates each aspect. Paradise Lost (once considered a monument to dead ideas) and Bunyan's work are found to speak with relevance to today's theological ferment; and the contributions of such modern thinkers as Kierkegaard, Niebuhr, and Tillich illumine the design of the two works. The author's imagination and literary insight give fresh perspective to two English classics. Originally published in 1960. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.